The Auriga project: the properties and formation mechanisms of disc galaxies across cosmic time - Grand, Robert J. J.; Springel, Volker; Pakmor, Rüdiger (Arxiv, 2017)
We introduce a suite of thirty cosmological magneto-hydrodynamical zoom simulations of the formation of galaxies in isolated Milky Way mass dark haloes. These were carried out with the moving mesh code \textlcsc{AREPO}, together with a comprehensive model for galaxy formation physics, including AGN feedback and magnetic fields, which produces realistic galaxy populations in large cosmological simulations. We demonstrate that our simulations reproduce a wide range of present-day observables, in particular, two component disc dominated galaxies with appropriate stellar masses, sizes, rotation curves, star formation rates and metallicities. We investigate the driving mechanisms that set present-day disc sizes/scale lengths, and find that they are related to the angular momentum of halo material. We show that the largest discs are produced by quiescent mergers that inspiral into the galaxy and deposit high angular momentum material into the pre-existing disc, simultaneously increasing the spin of dark matter and gas in the halo. More violent mergers and strong AGN feedback play roles in limiting disc size by destroying pre-existing discs and by suppressing gas accretion onto the outer disc, respectively. The most important factor that leads to compact discs, however, is simply a low angular momentum for the halo. In these cases, AGN feedback plays an important role in limiting central star formation and the formation of a massive bulge.